PENGARUH PGPRM (PLANT GROWTH PROMOTING RHIZOSPHERIC MICROORGANISMS) DAN MACAM MEDIA TANAM TERHADAP PERTUMBUHAN DAN HASIL BUNCIS PERANCIS - Umul Aiman; Bambang Sriwijaya; Arif nor fa’uzi (Universitas Muhammadiyah Semarang, 2015)
France Stringbean is one of good variaty vegetables which is export commodity. It has high consumption rate so that it needs to be risen of its growth and crops. One of the ways is by using various planting media and giving PGPRM. The purpose of this research is to learn the effects of planting media to the growth and the crops of France String Bean. This research conducted in the experiment garden of Agro Industry Faculty of Yogyakarta Mercu Buana University which is in the 90 meters above the sea level. This research uses Experimental Single Factor with eight different treatments which is arranged into RAL (Rancangan Acak Lengkap) by three times repetitions. The experiment factors are Sand+Soil+Compost (1:1:2) without PGPRM, Sand+Soil+Compost (1:1:1) without PGPRM, Sand+Soil+Compost (2:1:1) without PGPRM, Sand+Soil+Compost (0:1:1) without PGPRM, Sand+Soil+Compost (1:1:2) with PGPRM, Sand+Soil+Compost (1:1:1) with PGPRM, Sand+Soil+Compost (2:1:1) with PGPRM, Sand+Soil+Compost (0:1:1) with PGPRM. The result of this research showed that planting media and PGPRM do not have any differentiations to all variables of the growth and the crops of France String Bean.Keywords : France String Bean, Planting Media, PGPRM, growth, crops